PREVALENCE OF NORMAL ANATOMICAL VARIATION IN CIRCLE OF WILLIS AMONG PATIENTS UNDERGOING MAGNETIC RESONANCE ANGIOGRAPHY IN SHIFA INTERNATIONAL HOSPITAL (The Research of Medical Science Review, 2025)
Objectives: To determine the prevalence and pattern of normal anatomical variations of the Circle of Willis in adult patients undergoing magnetic resonance angiography (MRA) at Shifa International Hospital. Methodology: The study planned at Department of Radiology, Shifa International Hospital, Islamabad during the period of six months following ethical approval (June-Nov, 2023). This cross-sectional study was conducted on 235 patients aged 18–80 years undergoing MRA for various indications. Exclusion criteria included vascular malformations, tumors, diabetes, hypertension, and cerebrovascular events. MRA was performed using a 1.5 Tesla MRI scanner with 3D time-of-flight technique. Anatomical configurations were documented and analyzed using SPSS v20.0. Results: The most common COW variant was Type D (14.9%), followed by Type H (14.0%), B (13.2%), and A (12.3%). Complete circle configurations were uncommon. Variants were more frequent in posterior circulation. No statistically significant association was found between variant type and age (p=0.305) or gender (p=0.833), though variant P was more common in females and older individuals. Conclusion: Anatomical variations in the Circle of Willis are common in the local population, with posterior segment variations predominating. Knowledge of these patterns is essential for neurovascular planning and risk assessment.